Attributes of Society of Genitourinary Reconstructive Surgeons Fellows and Early Career Trajectory of the Recent Graduates - Baradaran, Nima; Cedars, Benjamin; Cohen, Andrew J; Buckley, Jill C; McCammon, Kurt A; Rourke, Keith; Breyer, Benjamin N (Urology practice, 2019)
We identified the attributes that the Society of Genitourinary Reconstructive Surgeons (GURS) fellowship directors prioritize in applicants. The secondary objective was to study the early career trajectory of recent GURS fellowship graduates. GURS fellowship directors and fellows from 2014 to 2018 were surveyed electronically using Qualtrics® software. We asked fellowship directors to rate 12 items for their importance in match selection on a Likert scale. Fellows were prompted for details of practice size, case mix and research time. We assessed research productivity based on published articles on PubMed® and Google Scholar™. Findings were summarized with descriptive statistics and continuous variables were reported as median with interquartile range. Fellowship directors (90% response rate) rated subjective personal qualities as more important compared to more objective measures and achievements. Personality (5, 5-5), overall interview performance (5, 4-5) and letters of recommendation (5, 4-5) were most important. About 4 papers were published during fellowship per fellow. However, research productivity did not persist during early career. Upon graduation the majority of graduates were the only reconstructionist at their practice, with approximately 40% of their operative time dedicated to such cases. While we identified a variety of practice settings, an academic career focusing on urethroplasty and male incontinence was the most common. Our data provide potential applicants with a better understanding of how to optimize their candidacy and what to expect in their early careers.